PENINGKATAN SUMBER DAYA MANUSIA MELALUI PELATIHAN KOMPUTER MICROSOFT EXCEL BAGI PERANGKAT DESA WIROGUNAN - Suhesti Ningsih; Maya Widyana Dewi (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2020)
The objectives and benefits obtained from this Microsoft Excel training are related to improving human resources (HR), especially village officials, namely providing knowledge and understanding of village officials on information technology and computers as well as increasing the ability and expertise of village apparatus in Wirogunan village, Kartasura district, Sukoharjo Regency in using technology. computers, especially Microsoft Excel application program. The problem is that the increasing number of residents with various educational backgrounds, social status, and professions makes the form of government services in the village more complex, while in service to the community and in making reports, the village apparatus of the Wirogunan village still has not fully utilized its potential especially in operationalize the Microsoft Excel program. The output target to be achieved is with the Microsoft Excel computer training program so that participants can understand and increase their knowledge in operating Microsoft Excel to carry out the task of compiling reports and also in serving the community. Keywords: Information Technology, Microsoft Excel, Village Tools